ANALISIS TERHADAP ANARKO-FEMINISME EMMA GOLDMAN - Mukhamad Syarif; Lathifah Sekar Sari (Sekolah Tinggi Agama Islam Sadra, 2022)
Anarchism, almost everyone when hearing the word in general must interpret it as a negative thing. Today anarchy is always defined as destructive actions, chaos, disorder, freedom and even rebellion. Historically, anarchy was intended as a political theory aimed at creating anarchy or the absence of a master, without a ruling king (independence over oneself). This study seeks to examine Emma Goldman's thoughts, especially in the idea of ​​Anarcho-feminism. This study uses a literature study method using a descriptive qualitative approach, which relies on library research and prioritizes descriptive processing to explain Emma Goldman's anarchism theory. The main source of this research is Emma Goldman's book “Anarchism & The Other Essay”, published in 1910 by Mother Earth Publishing, New York which was translated by Bima Satria Putra as “This Is Not My Revolution: A Collection of Anarcho-Feminism Essays” and other Emma Goldman books. The secondary data of this study were taken from various references such as books, journals, and articles relevant to this research. Primary data and secondary data were examined by descriptive methods, understanding (verstehen) and interpretation methods.